Effect of Salt Stress on the Pigment Content and Yield of Different Rice (Oryza sativa L.) Genotypes - Panda, D.; Ghosh, D. C.; Kar, M. (International Journal of Bio-resource and Stress Management, 2013)
A pot experiment was conducted at Institute of Agriculture, Visva-Bharati, Sriniketan during 2009 and 2010 to study the effect of salt stress on the pigment content and yield of different rice (oryza sativa L.) genotypes. The effect of induced salinity stress was studied on the pigment content of different rice genotypes like CSR-4, Canning-7, IR-29 and IR-64 under control and two levels of salinity (S1=40+20+20 mmol l-1 and S2=60+30+30 mmol l-1 of NaCl, Na2SO4 and CaCl2 respectively) in a pot experiment with complete randomized design. The experimental findings revealed that salinity stress decreased chlorophyll a, chlorophyll b, total chlorophyll and carotenoid content but increased the anthocyanin content in leaves of all the genotypes. The decrease in chlorophyll a, chlorophyll b, total chlorophyll and carotenoid content of leaves were more in IR-29 as compared to more tolerant genotypes CSR-4 and Canning-7. Grain yield also followed a similar trend. The tolerant cultivars Canning-7 and CSR-4 recorded significantly higher chlorophyll and carotenoid content as compared to the sensitive variety IR-29. The result further revealed that the grain yield of different rice genotypes under salt stress condition was positively correlated with chlorophyll and carotenoid content but negatively related to anthocyanin content of leaves.